Plant density and leaf morphology affects yield, fiber quality, and nutrition of cotton - Cordeiro, Carlos F. Dos S. [UNESP]; Echer, Fábio R.; Rodrigues, Daniel R. (FapUNIFESP (SciELO), 2023)
In sandy soils with frequent drought events, the choice of cultivar and plant density is crucial to improve water use efficiency and avoid losses in cotton yield and fiber quality. This study aimed to evaluate cotton cultivars’ yield and fiber quality at different plant densities. The study was carried out during two growing seasons (2017/2018 and 2018/2019) on sandy soil in southeastern Brazil. The cultivar TMG 47B2RF showed 27 and 29% higher yields under low and medium plant density, respectively, when compared with the highest plant density. The higher yield was due to the higher number of bolls in relation to the cultivar DBB 509B2RF. The boll weight of cultivar DBB 509B2RF was 23 and 22% higher under low and medium plant density, respectively. Fiber length and strength were higher in TMG 47B2RF compared to DBB 509B2RF. The leaf nutrient content was higher in DBB 509B2RF, except for Ca and Mg. When there is a regular rainfall, the low plant density results in higher yields, but intermediate plant density is the best option in cropping seasons with severe drought. The high density of plants in sandy soil environments was never a better option for none of the cultivars.
Densidade de plantas e morfologia foliar afetam a produtividade, qualidade e nutrição do algodoeiro
Keywords: cultivars; fiber strength; leaf morphology; plant nutrition